2005
DOI: 10.1007/s10493-004-1980-x
|View full text |Cite
|
Sign up to set email alerts
|

Diapause incidence in the two-spotted spider mite increases due to predator presence, not due to selective predation

Abstract: Diapause incidence in the two-spotted spider mite increases due to predator presence, not due to selective predation. Kroon, A.; Veenendaal, R.L.; Egas, C.J.M.; Bruin, J.; Sabelis, M.W. (2005). Diapause incidence in the twospotted spider mite increases due to predator presence, not due to selective predation. Experimental and Applied Acarology, 35, 73-81. DOI: 10.1007/s10493-004-1980-x General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Diapause has always been thought to emerge solely to overcome the winter season and to emerge in response to abiotic factors signalling the onset of the winter season, but it may also emerge in response to food scarcity and/or the risk of being eaten, as recently shown for the case of predator mites and fruit-tree red spider mites (Acari: Phytoseiidae, Tetranychidae) [5][6][7][8][9][10][11][12]. Although empirical proof of these diapause-governing principles is limited, they may well hold generally in ecological interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diapause has always been thought to emerge solely to overcome the winter season and to emerge in response to abiotic factors signalling the onset of the winter season, but it may also emerge in response to food scarcity and/or the risk of being eaten, as recently shown for the case of predator mites and fruit-tree red spider mites (Acari: Phytoseiidae, Tetranychidae) [5][6][7][8][9][10][11][12]. Although empirical proof of these diapause-governing principles is limited, they may well hold generally in ecological interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to conclude that the prey's decision to enter diapause is part of a game where the predator is the leader, and the prey needs to find an optimal response to the predator. Another complicating factor is that an early diapause raises the demands on the energy storage of the individual prey mite, which needs to cover a longer period before terminating diapause at the beginning of the next summer season-the energy level at diapause termination will determine the reproductive capacity of the prey mite [11]. Thus, the decision to enter diapause within a year will depend on the current internal energy store of the prey mite, as this will have farreaching consequences for winter survival and reproduction in the summer season of the next year.…”
Section: Introductionmentioning
confidence: 99%
“…Spider mites in refuges do not feed, thus precluding betrayal to their foes by feeding-induced plant signalling. Based on preliminary experiments (Kroon et al 2004(Kroon et al , 2005, we hypothesise that cues associated with predation enhance diapause induction in the two-spotted spider mite (Tetranychus urticae Koch). The ensuing change in metabolism would allow adult females to survive longer without food and to disperse into enemy-free space even if this harbours no food.…”
Section: Introductionmentioning
confidence: 99%
“…They may then move into refuges that are free of their enemies, but may lack food, and where survival may demand a switch to an energy-saving physiological state, such as the so-called diapause (Danks, 1987;Veerman, 1992). Diapause has always been thought to emerge solely to overcome the winter season and to emerge in response to abiotic factors signaling the onset of the winter season, but it may also emerge in response to food scarcity and/or the risk of predation, as it is believed to happen in the system of the so-called predatory mites (Acari: Phytoseiidae) and the fruit-tree red spider mites (Acari: Tetranychidae; prey mites) (Tauber et al, 1986;Danks, 1987;Veerman, 1992Veerman, , 1994Veerman, , 1985Kroon et al, 2004Kroon et al, , 2005Kroon et al, , 2008. Although empirical proof of these diapause-governing principles is limited, they may well hold more generally for ecological interactions in many other systems.…”
Section: Introductionmentioning
confidence: 99%
“…As without natural enemies, this diapause emerges in response to abiotic factors signaling the onset of the winter season, such as sufficient night length or low temperatures, it can be relatively easily induced in a greenhouse (Veerman, 1992(Veerman, , 1994. However, using another but similar species of spider mites, the two-spotted spider mite (Acari: Tetranychidae), it was shown that the decision to enter diapause also depends on abundance of its predators during summer (Kroon et al, 2004(Kroon et al, , 2005(Kroon et al, , 2008. From the point of view of the prey mite, going into diapause in response to predation risks makes intuitive sense as it faces a grim future with increasing predator densities and thus an increased risk of death: it may then do better by giving up reproduction, moving away from leaves to twigs and branches, and entering diapause.…”
Section: Introductionmentioning
confidence: 99%